Effects of botanicals against anthracnose and blight diseases of Houttuynia cordata Thunb - Saha, Trisha; Shamsi, Shamim (Journal of the Asiatic Society of Bangladesh, Science, 2016)
Anthracnose and blight were recorded on Houttuynia cordata Thunb. during April 2013 to December 2013. The isolated fungi from the symptomatic plants were identified as Alterneria alternata (Fr.) Keissler and Colletotrichum gloeosporoides (Penz.) Sacc. Ethanol leaf extracts of five plants viz.,Azadirachta indica L., Citrus limon L., Datura metel L., Sennaalata L. and Tagetes erecta L.were evaluated against the pathogenic fungi A. alternata and C. gloeosporoides at 5%, 10% and 20% concentrations in vitro. A. indica recorded as good inhibitor against the test fungi followed by C. limon, S. alata, D. metel and T.erecta. In vivo treatment also showed that A.indica is the most effective in controlling diseases at 10% concentration. The plants treated with A. indica were fresh and healthy up to one month of observation. J. Asiat. Soc. Bangladesh, Sci. 42(1): 41-48, June 2016